Spiritual Motivation in the Quran: Insights from ESQ 165 by Ary Ginanjar Agustian - Abdurrohim, Abdurrohim; Rohmana, Jajang A.; Zulaiha, Eni (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
Religion and spirituality are intertwined, with spirituality at the core of religious experience. Recent studies highlight the connection between spirituality and mental health, self-efficacy, and self-respect. In 2001, Ary Ginanjar Agustian introduced ESQ 165, a religious phenomenon aimed at enhancing human resources through spirituality. However, this concept faced criticism from some Islamic scholars, including Malaysian mufti Datuk Hj. Wan Zahidi bin Wan Teh, who argued it contradicts Islamic teachings. Conversely, research by Daromir Rudnyckij links ESQ 165 to